## Solving the Equation: (x+10)(x-4) = (x+2)^2

This equation presents a quadratic equation that can be solved using algebraic manipulation. Let's break down the steps:

### 1. Expand both sides of the equation

**Left side:**(x+10)(x-4) = x² - 4x + 10x - 40 = x² + 6x - 40**Right side:**(x+2)² = (x+2)(x+2) = x² + 2x + 2x + 4 = x² + 4x + 4

Now, the equation becomes: x² + 6x - 40 = x² + 4x + 4

### 2. Simplify the equation

Subtract x² from both sides: 6x - 40 = 4x + 4 Subtract 4x from both sides: 2x - 40 = 4 Add 40 to both sides: 2x = 44

### 3. Solve for x

Divide both sides by 2: x = 22

### Conclusion

Therefore, the solution to the equation (x+10)(x-4) = (x+2)² is **x = 22**.